Sea Kale—Crambe maritima L. - James M. Stephens (EDIS, 2003)
This document describes sea kale (Crambe maritima L.), a hardy perennial plant valued for its edible, asparagus-like shoots. It explains that sea kale is not well-suited to Florida’s climate due to its preference for cool, moist conditions. The document outlines its historical use as a scurvy preventative on sea voyages and details cultivation methods, including propagation from seeds or cuttings and blanching techniques to produce tender shoots. It also distinguishes sea kale from sea-kale cabbage, a different plant. Original publication date May 1994.